Aiming for life cycle sustainability assessment of cement‐based composites: A trend study for wall systems of carbon concrete: Dresden Nexus Conference 2020—Session 4—Circular economy for building with secondary construction materials to minimise resource use and land use. Issue 5 (28th December 2020) - Scope, Christoph; Guenther, Edeltraud; Schütz, Julia; Mielecke, Torsten; Mündecke, Eric; Schultze, Konstantin; Saling, Peter
Abstract: The narrative sustainable building is core message of European politics. Strategies discussed in this regard concern above all material minimization by using new more efficient manufacturing technologies, new form finding approaches for load‐bearing structures or new high‐performance materials. The goal of the research project V2.10, funded by the German Federal Ministry of Education and Research, refers to the latter by assessing the sustainability potential of building components made of innovative textile reinforced concrete. We conceptualized a life cycle sustainability assessment framework and applied it to variants of sandwich wall systems made of carbon concrete composites and steel‐reinforced concrete. Results indicate hotspots in technology and material choices that could be addressed by circular strategies, for example, refuse, reduce or recycling. Overall, one design variant made of carbon concrete composites is the best performing with respect to all dimensions of sustainability.